2012
DOI: 10.1111/j.1551-2916.2011.05051.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sialon‐Based Ceramics Toughened by Ferro‐Molybdenum Alloy

Abstract: High‐toughness Sialon ceramic matrix composites containing alloy second‐phase particles were fabricated by hot pressing at a relatively low temperature of 1600°C. Substantially improved fracture toughness of 8.0 MPa·m1/2 was achieved through the addition of varying amounts of ferro‐molybdenum alloy particles. The microstructure of the composites was characterized and crack propagation behavior was observed to understand the toughening mechanisms. The results showed that crack deflection and crack bridging are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…The sintering temperature of the specimen seems to be effectively lowered by increasing the TiO 2 content. Similar phenomenon was also reported for other dielectric ceramics [17,18]. Moreover, the sintering temperature for specimens with different TiO 2 additions to achieve the highest Q × f also corresponding to the highest density, suggesting the Q × f was mainly controlled by the density of specimens.…”
Section: Resultssupporting
confidence: 75%
“…The sintering temperature of the specimen seems to be effectively lowered by increasing the TiO 2 content. Similar phenomenon was also reported for other dielectric ceramics [17,18]. Moreover, the sintering temperature for specimens with different TiO 2 additions to achieve the highest Q × f also corresponding to the highest density, suggesting the Q × f was mainly controlled by the density of specimens.…”
Section: Resultssupporting
confidence: 75%
“…However, (Ca 1−x , Nd 2x/3 )TiO 3 ceramics also possessed a large positive f value, which precludes their usage in practice. Targeting at compensating their f values, an effective method has been developed to combine two or more compounds with negative and positive temperature coefficients, respectively, to form solid solutions or mixed phases [7][8][9][10][11][12], such as ZnAl 2 O 4 -TiO 2 , (Ca, Mg)SiO 3 -CaTiO 3 , (Ca, Sm)TiO 3 -TiO 3 , La(Mg 1/2 Ti 1/2 )O 3 -(Na 1/2 Nd 1/2 )TiO 3 , TiO 2 -NiNb 2 O 6 , and Zn 2 TiO 4 -TiO 2 complex ceramics. Results exhibited that zero f values could be obtained at the proper composition ratio between the end members.…”
Section: Introductionmentioning
confidence: 99%
“…For RBSN ceramics, many metals (including iron) can promote the nitridation of silicon [11][12][13][14], but iron in Si 3 N 4 -based ceramics might decrease the strength [15]. Huang reported that the addition of the FeMo alloy could improve the strength and fracture toughness of hot pressed b-Sialon [16,17], but hot pressed sintering is very difficult in engineering applications. Therefore, a reaction bonding method to produce b-Sialon strengthened and toughened by FeMo alloy will be of interest.…”
Section: Introductionmentioning
confidence: 98%